Vaccination with an in vitro culture attenuated Babesia bovis strain safely protects highly susceptible adult cattle against acute bovine babesiosis - Bastos, Reginaldo G.; Capelli-Peixoto, Janaina; Laughery, Jacob M.; Suarez, Carlos E.; Ueti, Massaro W. (Frontiers in Immunology, 2023)
Live in vivo attenuated Babesia bovis vaccines produced by sequential passages in splenectomized calves have historically been used to control acute bovine babesiosis in endemic areas worldwide. However, several constraints prevent the widespread use of these vaccines, including the need for several splenectomized calves to produce vaccine batches, and potential inconsistent parasite attenuation, which contraindicates their use for highly Babesia-susceptible adult cattle. Thus, the use of vaccines based on well-defined in vitro culture attenuated B. bovis strains emerges as a more sustainable and efficient alternative. Previous work demonstrated that the culture attenuated strain Att-S74-T3Bo is non-tick transmissible and able to safely protect calves against needle challenge with a B. bovis virulent strain. Herein we evaluated safety and efficacy of Att-S74-T3Bo in preventing acute babesiosis in adult (>1.5 year of age) cattle. Results demonstrated that Att-S74-T3Bo vaccination of adult animals (n=5) induced self-limiting signs of acute infection and protected the vaccinated animals against challenge with the homologous virulent B. bovis strain Vir-S74-T3Bo. Att-S74-T3Bo-vaccinated adult cattle developed significant (P<0.05) monocytosis, with concomitant neutropenia and CD4 + leukopenia, in peripheral blood early after vaccination. Also, vaccinated animals developed a specific signature of pro-and anti-inflammatory cytokine expression in peripheral blood and significant levels of IgM, total IgG, IgG1, and IgG2 against the B. bovis immunodominant antigen RAP-1 CT. Strikingly, none of the vaccinated animals showed any signs of acute babesiosis after challenge with Vir-S74-T3Bo. In contrast, control adult cattle (n=5) showed pathognomonic symptoms of acute babesiosis, and significant decrease (P<0.05) in lymphocytes, monocytes, and neutrophils, starting on day 7 post-challenge. All control animals developed severe acute disease and were euthanized on days 10 through 12 days post-challenge. Thus, evidence from this study indicates that Att-S74-T3Bo safely protects highly susceptible adult cattle against challenge with a homologous virulent strain of B. bovis. In conclusion, Att-S74-T3Bo may be considered as a potential efficient and sustainable attenuated candidate vaccine strain to control acute bovine babesiosis in highly susceptible adult cattle. Future studies should focus on increasing the number of animals vaccinated, duration of immunity, and efficacy of this attenuated strain against heterologous virulent parasite strains.